2018
DOI: 10.1016/j.cortex.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

An autistic-like profile of attention and perception in synaesthesia

Abstract: Synaesthesia and autism are two neurodevelopmental conditions that have been shown to co-occur more than expected by chance. The studies reported here test the hypothesis that increased sensory sensitivity and enhanced Attention-to-detail are core cognitive features that are shared between them. In Study 1, we administer self-report measures of sensory sensitivity and autistic traits (the Autism Spectrum Quotient, AQ) to a large heterogeneous sample of synaesthetes. Both sensory sensitivity and the Attention-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
74
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 50 publications
17
74
4
Order By: Relevance
“…Hughes et al (2017) found that synesthesia in autism is linked to savant skills. These results are further supported by Ward et al (2017), who found that synesthetes have enhanced perception and attention and exhibit autistic-like impairments, too. It has been found that axonal connections between V4, which is involved in color processing, and the so-called 'grapheme area' are denser in synesthetes than in controls (Rouw and Scholte, 2007).…”
Section: Synesthesiasupporting
confidence: 66%
“…Hughes et al (2017) found that synesthesia in autism is linked to savant skills. These results are further supported by Ward et al (2017), who found that synesthetes have enhanced perception and attention and exhibit autistic-like impairments, too. It has been found that axonal connections between V4, which is involved in color processing, and the so-called 'grapheme area' are denser in synesthetes than in controls (Rouw and Scholte, 2007).…”
Section: Synesthesiasupporting
confidence: 66%
“…(), who found a correlation between convergent verbal creativity and the amount of multiple types of synaesthesia and with Ward et al . (). The finding that sound‐colour synaesthetes are specifically more involved in art, but do not score significantly higher in divergent creativity, is also in line with Ward, Thompson‐Lake et al .…”
Section: Discussionmentioning
confidence: 97%
“…(), Ward, Hovard, Jones, and Rothen () and Ward et al . () who found differences in cognitive performance and cognitive style for different types of synaesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important hypothesis states that synaesthesia and autism share atypical sensory sensitivity and altered sensory perception [6,7]. In autism research, increased attention to sensory abnormalities (e.g.…”
Section: Introductionmentioning
confidence: 99%